Análise de atividades de educação ambiental do Parque Zoológico Municipal Quinzinho de Barros pela perspectiva da Educação ambiental crítico-transformadora via temas geradores - Oliveira, Aline Recchia de (Universidade Federal de São Carlos, 2023)
Education is the base that constitutes and transforms human beings. Its importance in the individual and social life of individuals is indisputable, requiring that the political-pedagogical development of teaching and learning have a strong foundation in a perspective that will lead all individuals to the place of participants in the construction of their own education and their community, their culture and their country, which manages to penetrate reality and make sense to students when the contents are developed and worked on, and which generates the construction of knowledge that leads individuals to criticality, giving them the power to reflect, problematize, unveil contradictions and overcome their reality, transforming it. With these perspectives, Environmental Education of the Critical-transformative aspect is based on the reflections and educational practices of educator Paulo Freire. However, the present work aims to verify if the EE activities of the Parque Zoológico Municipal Quinzinho de Barros, in the city of Sorocaba, approach or distance themselves from the pedagogical policy proposal of the Environmental Education of the Critical-transformative, since it is believed that zoos are places with great potential to attract the public and, therefore, should develop their EE activities in the best possible way with an audience of different age groups. To this end, the reports of activities carried out by the institution between 2008 and 2019 were analyzed, pointing out the limits and potential of these activities, based on the categories: dialogue, generating themes and transforming action. The results point to a distancing from the perspective of Critical-Transforming Environmental Education via generative themes, with regard to the categories dialogue and transforming action, and to a potential approximation of the category generative themes, which happened much more through the totalizing analysis than was proposed and worked on in Environmental Education activities at the Quinzinho de Barros Municipal Zoological Park, based on the foundations of Critical-Transforming Environmental Education via generative themes, rather than the prior adoption of this framework for the development of these activities.
Analysis of environmental education activities of the Quinzinho de Barros Municipal Zoological Park from the perspective of critical-transformative environmental education through generating themes
Keywords: Educação ambiental; Diálogo; Tema gerador; Ação transformadora; Paulo Freire; Environmental education; Dialogue; Generator theme; Transforming action; Paulo Freire; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO